AutoCAD 2017 Essential Training. - Bryant, Shaun (linkedin.com, 2016)
Learn how to create 2D and 3D drawings using AutoCAD 2017. This course can help both AutoCAD beginners and pros use AutoCAD 2017 effectively in any industry.